Blockchain for Organic Food Traceability: Case Studies on Drivers and Challenges - van Hilten, Mireille; Ongena, Guido; Ravesteijn, Pascal (Frontiers in Blockchain, 2020)
Purpose – This article evaluates the application of Blockchain technology to improve organic or fair-trade food traceability from ‘Farm to Fork’ in light of European regulations. This study aims to shed light on the challenges in the organic food chain to overcome, the drivers for Blockchain technology and the challenges in current projects. Design/methodology/approach – For this research a case study approach was taken in which four Blockchain projects were evaluated on their success. Findings - Organic food supply chain companies aiming to improve food traceability, with Blockchain face two key decisions, depending on the characteristics of the organic value chain in regard to (1) optimizing chain partner collaboration and (2) the selection of which data to capture in the Blockchain. Other challenges were data confidentiality, validation of data inputs and interoperability. Easy verification of certification data, accountability, improved risk management, insight into trade transactions, simplified data collection and exchange and improved communication account for the benefits. Regardless of what drives companies towards whole chain traceability, for example customer satisfaction, it does not necessarily require Blockchain technology. Blockchain does enable faster food traceability. which is expected to be more applicable to a complex food supply chain. Research limitations/implications – The limitations of this study are represented mainly by the scarcity of organic blockchain projects aiming to minimize pesticide inputs and limited availability of information of commercial projects. Practical implications – This study shows that Blockchain is currently successfully being implemented on a small scale to create whole chain traceability of organic and fair-trade food. Originality/value - This research addresses the intersection of food supply chain and organic food quality and certification. The focus on origin information and importance of organic data elements may underpin other research on EU regulations in relation to food traceability, adding value to the body of knowledge on the current status of Blockchain technology.